POSITIVE AND NEGATIVE USAGE OF THE WORD "GUEST" IN UZBEK AND ENGLISH PROVERBS (Scientific journal of the Fergana State University, 2024)
This article analyzes the positive and negative usage of the word "guest" in Uzbek and English proverbs and the importance of hospitality in our nation. The article provides information and examples of how hospitality reflects the unique meaning, manners and spirituality of our society. The text covers the manners, composition, traditions and reception of guests.